LABOR ABSORPTION AND CONTRIBUTION OF THE PROCESSING INDUSTRY SECTOR TO ECONOMIC GROWTH IN THE PROVINCE OF THE BANGKA BELITUNG ISLAND - Wulandari, Ayu; Hidayati, Hidayati (Fakultas Ekonomi dan Bisnis Universitas Lampung, 2023)
This research aims to analyze the absorption of labor and the contribution of the processing industry sector to economic growth in the Province of the Bangka Belitung Islands. The data used in this research is secondary data of time series for the period 2012 to 2021 which is sourced from the Indonesia Statistics (BPS) of the Bangka Belitung Islands Province and literature studies. The analytical method used to calculate the elasticity of employment opportunities to see the absorption of labor and the proportion method to see the contribution of economic growth this research used the proportion method. The results showed that the Manpower and Workforce Growth Rate in the processing industry sector in the Province of the Bangka Belitung Islands in 2009-2021 is fluctuated. The average distribution of workers in the processing industry sector is 6.45 percent. The highest distribution of labor in the processing industry sector occurred in 2020 was 8.19 percent and the lowest in 2010 at 4.47 percent. The absorption of labor in the processing industry sector is mostly absorbed in the tin metal processing industry. The processing industry sector is one of the five sectors that have the largest contribution to the economic structure of the Bangka Belitung Islands over the last 10 years besides agriculture sector, trade sector, mining sector, and construction sector. The average elasticity of employment opportunities in the Province of the Bangka Belitung Islands is 315.41 percent.